2015
DOI: 10.1001/jama.2015.8035
|View full text |Cite|
|
Sign up to set email alerts
|

Mortality, Hospitalizations, and Expenditures for the Medicare Population Aged 65 Years or Older, 1999-2013

Abstract: In a period of dynamic change in health care technology, delivery, and behaviors, tracking trends in health and health care can provide a perspective on what is being achieved.OBJECTIVE To comprehensively describe national trends in mortality, hospitalizations, and expenditures in the Medicare fee-for-service population between 1999 and 2013. DESIGN, SETTING, AND PARTICIPANTS Serial cross-sectional analysis of Medicare beneficiaries aged 65 years or older between 1999 and 2013 using Medicare denominator and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 24 publications
5
102
1
Order By: Relevance
“…29 This finding may be explained by recent evidence that has suggested that select low-risk PE patients may utilize outpatient care, including newer modalities of subcutaneous heparin delivery and oral anticoagulation therapy, as a safe and effective alternative to inpatient treatment. 8,9 Interestingly, despite a decrease in the length of stay, adjusted 30-day readmission rates remained fairly stable over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…29 This finding may be explained by recent evidence that has suggested that select low-risk PE patients may utilize outpatient care, including newer modalities of subcutaneous heparin delivery and oral anticoagulation therapy, as a safe and effective alternative to inpatient treatment. 8,9 Interestingly, despite a decrease in the length of stay, adjusted 30-day readmission rates remained fairly stable over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to see how the "medical ecology" could be altered by technologic advances. 16 It appears that there have been gains in health outcomes among the Medicare population, 26 but gaps in health with comparator nations appear to be increasing. 6 It is also unknown to what extent the increases in expenditure are related to increased costs for treatments, drugs, and tests of similar efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant to population health management (also known as "population medicine"), which focuses on improving the health of clinically defined groups. 4 Although the value of health care is relevant throughout the continuum of illness, costs are particularly high during the last year of life 5 -and if the value of certain interventions, such as screening for colorectal cancer, does not accrue for many years, then life expectancy should be considered when deciding to screen.…”
Section: What Population Health Can Learn From Palliative Carementioning
confidence: 99%